Ammonium Sensing Patch with Ultrawide Linear Range and Eliminated Interference for Universal Body Fluids Analysis - Huang, Mingli; Ma, Xiaohao; Wu, Zongze; Li, Jirong; Shi, Yuqing; Yang, Teng; Xu, Jiarun; Wang, Shuhan; Lv, Kongpeng; Lin, Yuanjing (Nano-Micro Letters, 2024)
Ammonium level in body fluids serves as one of the critical biomarkers for healthcare, especially those relative to liver diseases. The continuous and real-time monitoring in both invasive and non-invasive manners is highly desired, while the ammonium concentrations vary largely in different body fluids. Besides, the sensing reliability based on ion-selective biosensors can be significantly interfered by potassium ions. To tackle these challenges, a flexible and biocompatible sensing patch for wireless ammonium level sensing was reported with an ultrawide linear range for universal body fluids including blood, tears, saliva, sweat and urine. The as-prepared biocompatible sensors deliver a reliable sensitivity of 58.7 mV decade−1 in the range of 1–100 mM and a desirable selectivity coefficient of 0.11 in the interference of potassium ions, attributed to the cross-calibration within the sensors array. The sensor’s biocompatibility was validated by the cell growth on the sensor surface (> 80%), hemolysis rates (< 5%), negligible cellular inflammatory responses and weight changes of the mice with implanted sensors. Such biocompatible sensors with ultrawide linear range and desirable selectivity open up new possibility of highly compatible biomarker analysis via different body fluids in versatile approaches. Highlights: 1 The as-prepared sensors can detect NH4+ in the body fluids with a high sensitivity of 58.7 mV decade−1 and an ultrawide detection range of 1–100 mM. 2 The biocompatible sensors exhibit desirable biocompatibility and minimal toxicity for continuous and long-term monitoring. 3 The average detection error of the integrated and wireless biosensing patch was 13.2%, and body fluid detection accuracy is improved by more than 18% after cross-calibration.